Pengaruh Kualitas Produk, Citra Merek Terhadap Keputusan Pembelian Lapis Kukus Pahlawan Surabaya - Ridha Ibnutama; Hery Pudjoprastyono (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
This study aims to analyze the influence of Product Quality and Brand Image on the Purchasing Decision of The Sidoarjo branch of Lapis Kukus Pahlawan Surabaya. The population used as the object of study was the consumers of the Sidoarjo branch of Lapis Kukus Pahlawan Surabaya with sample calculations through purposive sampling techniques through the lemeshow calculation formula obtained by 100 respondents. The quantitative method was chosen by the SEM (Structural Equation Modeling) data analysis technique using the PLS (Partial Least Squares) software application. The research proved that product quality influences purchase decisions for Lapis Kukus Palawan Surabaya and brand image influences purchase decisions for Lapis Kukus Palawan Surabaya Sidoarjo.